Pengenalan Kosakata Bahasa Inggris Bertema Lingkungan Sekolah di Sekolah Dasar - Retnowaty Retnowaty; Prita Indriawati; Kiftian Hady Prasetya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2020)
English vocabulary mastery in elementary school students is quite minimal. This can happen because they have not yet learned English because the lessons have been removed from the elementary school curriculum starting in 2014. The implementation team was restless and wanted to introduce English early on to students, especially at SDN 012 West Balikpapan as a form of initial recognition in order to survive and able to compete in junior high school. The method used is to provide theory and practice to the target audience. The activity of introducing English vocabulary on the theme of the school environment is carried out through face to face with the delivery of material through the lecture method followed by guidance, practice, and evaluation in understanding vocabulary with the themes of alphabets, numbers, colors and school subjects, School Things, and People in School. The results of community service activities carried out at SDN 012 West Balikpapan provide considerable benefits and are needed by students at the school. School principals, teachers, and students expect this activity to be carried out continuously through mentoring activities and forms of English language training and other lessons. Language Training is one form of non-formal education that is very important and useful for students to get to know English that still feels foreign.